Propositions on the Optimal Number of Q-Graders and R-Graders - Lucas Louzada Pereira; Rogério Carvalho Guarçoni; Gustavo Soares de Souza; Dério Brioschi Junior; Taís Rizzo Moreira; Carla Schwengber ten Caten (Journal of Food Quality, 2018)
Sensory analysis or cup testing has been widely used in the coffee production chain for the validation of final quality. The tasters are responsible for defining the patterns and qualitative profiles of the drink based on the sensorial analysis and according to their gustatory sensibilities, which are often acquired by professional experience. However, the literature has not discussed in detail the relationship between the number of tasters and the consistency of sensorial analysis. Thus, using the bootstrap simulation methodology to estimate the optimum plot size, this study quantifies and proposes a specific number of tasters for the process of sensorial analysis of specialty coffees. The results indicate that the use of 6 tasters is sufficient to conduct sensorial analysis following SCA and BSCA protocol for coffees in the Arabica group, as well as 6 tasters for coil and Conilon coffees. From this number, no gains in precision are observed in the process of sensorial analysis of coffee with addition tasters.